Antioxidation and anti-ageing activities of different stereoisomeric astaxanthin in vitro and in vivo. (August 2016) - Liu, Xiaojuan; Luo, Qingxin; Rakariyatham, Kanyasiri; Cao, Yong; Goulette, Timothy; Liu, Xin; Xiao, Hang
Highlights: There were significant differences among three stereoisomeric AST both in vitro and in vivo . S AST exhibited the strongest antioxidation and anti-ageing activities. Anti-ageing activities of three stereoisomeric AST do not cause adverse effects on the physiological functions of C. elegans . Abstract: Astaxanthin (AST) is a potent antioxidant with different stereoisomers in nature. However, there have been no reports about the functional activities of different stereoisomers so far. In this study, the antioxidant and anti-ageing activities of 3S, 3'S ( S ), 3R, 3'R ( R ), and mixture ( M ) AST were evaluated in chemical-based assays, cellular antioxidant assays (CAA), and an organism-based model. S AST exhibited the strongest activity in chemical assays and CAA. The median lifespan of Caenorhabditis elegans fed with S, R and M AST was found to increase by 27.61%, 25.25% and 22.69%, respectively. The three stereoisomeric AST did not cause adverse effects on the physiological functions of C . elegans . A decreasing trend of intracellular ROS accumulation caused by AST treatment was accompanied by the prolonged lifespan. Our results provided mechanistic information on the antioxidation and anti-ageing activities of different stereoisomeric AST, which is useful for rational utilization of AST in functional food.